Development of 5G LDPC Experimental Kit - Thanat Srisupha; Krittiyaporn Mueadkhunthod; Watid Phakphisut; Sirawit Khittiwitchayakul; Kidsanapong Puntsri; Thanomsak Sopon (2022 37th International Technical Conference on Circuits/Systems, Computers and Communications (ITC-CSCC), 2022)
In this work, we develop the 5G LDPC experimental kit to demonstrate the encoding processes of LDPC codes in 5G new radio. The experimental kit consists of a graphical user interface (GUI) and an FPGA development board. Any parameters defined in the 5G new radio can be configured and their encoding results are presented in the GUI. We also develop the 5G LDPC encoder as the software module integrated within the GUI. The user can select the software or hardware for the 5G LDPC encoder. The experimental kit is simple to use and no need any complicated setups. We believe that the experimental kit would be useful to anyone interested in the LDPC 5G NR standard.
Keywords: Error Correcting Code Techniques; Advanced Wireless Communication Techniques; Advanced MIMO Systems Optimization